Influência do desbalanço superóxido-peróxido de hidrogênio na resiliência psico-comportamental: um estudo translacional - Jung, Ivo Emilio da Cruz (2021)
Introduction: The psychosocial stress is considered a trigger in the development of several non-communicable chronic diseases (NCDs), especially psychiatric disorders such as Depression. However, stressful events are perceived differently among people. This ability to recover is called resilience and appears to be genetically influenced, including the Val16Ala polymorphism, of the antioxidant enzyme SOD-2 which can generate 3 different genotypes AA, VV, AV, which influence the Superoxide-Hydrogen Peroxide (S-HP) balance in the body. Objectives: To evaluate, through a translational study, the genetic and pharmacological influence of the S-HP imbalance. Methods: The first study was a case-control study in which the association between the Val16Ala- SOD2 polymorphism with lower resilience (identified by self-perceived exposure to stress) and risk of depression in the evaluated elderly. The second study sought to investigate whether the different genotypes of the Val16Ala- SOD2 polymorphism could influence the basal levels of molecules of the Hypothalamus-Pituitary Adrenal axis associated with stress response (cortisol, ACTH, DHEA) and of the neurotrophic factor BDNF in 90 young adults without previous history of psychiatric disorders. The third study was conducted in Californian red earthworms (Eisenia Fetida). Results: The first study showed that carriers of the VV-SOD2 genotype, regardless of the status of depression, also perceived themselves as more stressed than the others. In addition, elderly people with this genotype had a higher frequency of polypharmacy and daily drug intake. The set of results supported the hypothesis that S-HP imbalance associated with chronic inflammation may increase the risk of self-perceived stress, which indicates lower resilience and the risk of depression in elderly people. In the second study, we observed that carriers of the VV-SOD2 genotype had higher morning cortisol and ACTH levels and lower levels of DHEA and BDNF than adults carrying the A-allele (AA and AV-SOD2). These results suggested that the S-HP imbalance associated with the Val16Ala-SOD2 polymorphism could modulate markers of the HPA axis and neurogenesis regardless of the individual being stressed or depressed. Finally, the investigation carried out in the experimental model E. Fetida showed relevant results regarding the role of the S-HP unbalance in the oxidativeinflammatory metabolism and in the survival behavior. The S-HP unbalance, both induced by rotenone (VV-like) and porphyrin (AA-like) caused important alterations in the oxidative and inflammatory metabolism and in the survival behavior of earthworms. In summary, while AA-like earthworms showed a potential improvement in their immunocompetence and in life-threatening situations, VV-like earthworms presented a profile similar to chronic inflammation and a lower capacity for behavioral protection against exposure to environmental stress. These results suggested that the S-HP imbalance could modulate the immune system and the behavioral response to stress via alterations in immune metabolism. Conclusion: Despite the methodological limitations of each study, the set of results suggests that inflammatory changes produced by S-HP unbalance could induce reduced states of psychobehavioral resilience both in human beings and in primitive experimental models, as is the case with earthworms. These results are relevant as they can be used as support for investigations that lead to the development of therapeutic strategies mainly associated with cognitive-behavioral psychotherapy that attenuate the sensitivity of patients with the VV genotype to psychosocial stressors and help to alleviate the debilitating symptoms of patients diagnosed with depression.